Urgency and Impact Election Simultaneously Operate - Imam Supriyanto; Mufidah Mufidah (JOURNAL of LEGAL RESEARCH, 2021)
People's sovereignty in a democratic system is marked by the implementation of general elections. Elections are an embodiment of a democratic system that has received responses from various countries as an ideal means or mechanism in the framework of a peaceful and orderly power transfer process. By holding elections, it is hoped that the process of transferring power in a country will run well. Therefore, the election received serious attention from various groups, so that the idea of simultaneous elections emerged. This study uses a qualitative method with a statutory approach. The results of the study state that simultaneous national elections not only have implications for the realm of constitutional law or political administration but also have a negative impact on their implementation.